TERRORISM IN THE NEWS FRAME - Oktavia Margareta; Sri Narti; Sapta Sari (Perkumpulan Dosen Muda (PDM) Bengkulu, 2020)
The research objective entitled terrorism in the news frame (framing analysis of the news of the legal verdict of inmate terrorism Abu Afif on detiknews.com as the online media edition September 13 2018)was to find out how detiknwes.com as the online media framed the news of Abu Afif terrorist prisoners. This study focuses on reporting on the legal verdict of inmete terrorism prisoner Abu Afif. This research is aqualitativ content analysis research. The method used is framing analysis using the zhongdang pan and gerald M. Kosicki models. The flaming method is used to analyze the text of the media because there is a prominence of certain infotmation. Based on the results of the analysis of graming news developed by detiknews.com on the news of Abu Afifs convictions by means of: selection of news titles, selection of news sources, selection detiknews.com in highlighting news tends to play neutral and not to do analysis and sharp reviews. Framing detiknews.com raises legal issuse, and has nothing to do with politics and religion. Therefore, the frame used by detiknews.com is the legal frame.